Associations of lamplight exposure during sleep and sleep duration with attention-deficit/hyperactivity disorder among preschool children in China - Jiang, Hui; Yu, Bin; Liu, Yuanyang; Gao, Hui; Song, Ruijuan; Tan, Siyue; Han, Shufen; Zuo, Hui (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to examine the associations of exposure to light while sleeping at night and different sleep durations with attention-deficit/hyperactivity disorder (ADHD) among preschool children in China.MethodsA cross-sectional study including 4197 preschool children (2190 boys and 2007 girls) was conducted in 2021. Lamplight exposure during sleep and sleep duration were collected via a validated questionnaire. ADHD was assessed using the Conners Parental Symptom Questionnaire (PSQ). Associations of exposure to light while sleeping and sleep duration with ADHD were examined by multivariable logistic regression models.ResultsThe overall prevalence of ADHD was 3.7%. Compared to the children who slept with the lamplight off at night, those who slept with the lamplight on ≥3 nights/week were more likely to have ADHD after multivariable adjustment (OR=3.37; 95% CI: 1.95, 5.82; P-trend <0.001). The risk associations of lamplight exposure during sleep with ADHD were similar in subgroups stratified by sex, picky eating, gestational hyperglycemia, and gestational anemia. Moreover, compared to the children with sleep duration of 10-12 hours/day, adjusted OR for ADHD was 1.64 (95% CI: 1.14, 2.35) for those with sleep duration <10 hours/day and 2.69 (95% CI: 1.12, 6.44) for those who slept>12 hours/day.DiscussionLamplight exposure during sleep at night was positively associated with ADHD among preschool children. Also, both sleep duration of <10 hours/day and >12 hours/day increased the likelihood of ADHD. Our novel findings suggest the importance of sleeping habit on the prevention of ADHD. Prospective and interventional studies are warranted to elucidate the observed associations.